2021
DOI: 10.1136/bmjopen-2021-049199
|View full text |Cite
|
Sign up to set email alerts
|

Is patient participation in multidisciplinary tumour conferences associated with their information needs? A multicentre prospective observational study

Abstract: ObjectivesTo determine the association between participation of patients with breast cancer and patients with gynaecological cancer in their own multidisciplinary tumour conference (MTC) and their information needs with regard to their disease and treatment options.MethodsThis is a prospective observational study that took place at six breast cancer and gynaecological cancer centres in North Rhine-Westphalia, Germany. Patient inclusion criteria included a minimum age of 18 years and at least one diagnosis of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The decision-making process involves a rational distancing 25 that takes little account of patients’ preferences at first glance. Nevertheless, physician and patient can share information and interact before or after a MCM 26 and a recent study has shown that patient participation in MCM could not change their desire for information 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The decision-making process involves a rational distancing 25 that takes little account of patients’ preferences at first glance. Nevertheless, physician and patient can share information and interact before or after a MCM 26 and a recent study has shown that patient participation in MCM could not change their desire for information 27 .…”
Section: Introductionmentioning
confidence: 99%